PENERAPAN PERMAINAN POMBAR UNTUK MENINGKATKAN KEMAMPUAN KONSENTRASI ANAK USIA 4-5 TAHUN DI RA AL- MUSTAQIM BRINGIN BENDO SIDOARJO - Ainun Mufidah; Ahmad Fachrurrazi (Jurnal Al-Fatih, 2025)
Concentration ability is important for children's cognitive development, but early childhood generally has a short attention span. Thus, educators need to design effective learning strategies, such as learning while playing methods. This study addresses the low concentration of early childhood children with Pombar media (pom-pom with pictures), a colorful game with animal pictures to attract attention and train concentration through color matching activities. Using a quantitative descriptive approach with a pre-test and post-test design, this study was conducted on 15 children aged 4-5 years at RA Al-Mustaqim Bringin Bendo Sidoarjo. The research instruments include observation and documentation. The purpose of this study was to improve concentration and recognize colors, distinguish colors, and adjust colors on Pombar. The results showed that there was progress in children's concentration after using Pombar, with a percentage increase of 61.33% in indicators and 61.34% in minutes. This proves that Pombar is effective in improving children's concentration.